Um estudo sobre a influência da interação gravitacional nos estados de Rydberg no cenário de dimensões extras - Maciel, Eugênio Bastos (2020)
It has been argued that precise measurements of optical transition frequencies between Rydberg states of hydrogen-like ions could be used to obtain an improved value of the Rydberg constant and even to test Quantum Electrodynamics (QED) theory more accurately, by avoiding the uncertainties about the proton radius. Motivated by this perspective, we investigate the influence of the gravitational interaction on the energy levels of Hydrogen-like ions in Rydberg states within the context of the braneworld models. As it is known, in this scenario, the gravitational interaction is amplied in short distances. We show that, for Rydberg states, the main contribution for the gravitational potential energy does not come from the rest energy concentrated on the nucleus but from the energy of the electromagnetic field created by its electrical charge, which is spread in space The reason is connected to the fact that, when the ion is in a Rydberg state with high angular momentum, the gravitational potential energy is not computable in zero-width brane approximation due to the gravitational of the electrovacuum in which the lepton is moving. Considering a thick brane scenario, we calculate the gravitational potential energy associated to the nucleus charge in terms of the confinement parameter of the electric field in the brane. We show that the gravitational effects on the energy levels of a Rydberg state can be amplified by the extra dimensions even when the compactfication scale of the hidden dimensions is shorter than the Bohr radius.